The summer place : [large type] a novel - Weiner, Jennifer (Center Point Large Print, 2022)
"When her twenty-two-year-old stepdaughter announces her engagement to her pandemic boyfriend, Sarah Danhauser is shocked. But the wheels are in motion. Headstrong Ruby has already set a date (just three months away!) and spoken to her beloved safta, Sarah's mother Veronica, about having the wedding at the family's beach house on Cape Cod. Ruby has always known exactly what she wants, but as the wedding date approaches, she finds herself grappling with the wounds left by the mother who walked out when she was a baby. Veronica ends up facing unexpected news, thanks to her meddling sister, and must revisit the choices she made long ago, when she was a bestselling novelist with a different life. Sarah's twin brother, Sam, is recovering from a terrible loss, and confronting big questions about who he is - questions he hopes to resolve during his stay on the Cape. Sarah's husband, Eli, who's been inexplicably distant during the pandemic, confronts the consequences of a long ago lapse from his typical good-guy behavior. When the wedding day arrives, lovers are revealed as their true selves, misunderstandings take on a life of their own, and secrets come to light. There are confrontations and revelations that will touch each member of the extended family, ensuring that nothing will ever be the same."--